Hubungan Ukuran Lingkar Pinggang terhadap Nilai Volume Oksigen Maksimal (Vo2maks) pada Pria dengan Pekerjaan Aktivitas Fisik Tinggi - Irfan Darfika Lubis; Najwa Izza Qolbi Nada (Jurnal Ilmu Kedokteran dan Kesehatan Indonesia, 2026)
Introduction: Maximal oxygen volume (VO2max) is the capability of the cardiorespiratory system to deliver oxygen to muscle mitochondria, which is directly proportional to the level of stamina and is obtained from physical activity. Central obesity, which is characterized by excessive accumulation of visceral fat, can cause decreased stamina, so individuals with central obesity tend to have lower VO2max values. VO2max values can be determined by body composition, such as waist circumference, which is an indicator of central obesity. Methods: This study used an observational analytical design with a cross-sectional approach and involved 54 male respondents with high physical activity jobs who worked as building construction workers in Medan City, North Sumatra Province. Waist circumference measurements were carried out using a measuring tape, while VO2max was assessed using a 6-minute walk test. Statistical analysis was performed using the Spearman correlation test with a significance level of 0.05. Results: A total of 47 respondents (87%) had a normal waist circumference, 31 respondents (57.4%) had a fair VO2max, and 16 respondents (29.6%) had an average VO2max. The analysis showed a significant relationship between waist circumference and VO2max, with a P value of 0.000 (P<0.05) and R = -0.658. Conclusion: There is a strong and significant negative correlation between waist circumference and VO2max. This indicates that a larger waist circumference results in a lower VO2max, and a smaller waist circumference results in a higher VO2max.